The Determinant of Moslem’s Decision in Performing Commerce Zakat Payment: Case Study in Malang City, East Java Province - Santi Merlinda; Umar Burhan; Marlina Ekawaty (Institute of Research and Community Service, University of Brawijaya)
Zakat has known as one of the vital instrument in economic that holds some benefits for increasing aggregate demand, expanding job opportunities, reducing poverty and triggering economic growth. As one of the large cities in East Java Province, Malang has a potential issue through commerce zakat which most of the people’s livelihood engaged to and composition of regional income (PDRB) is dominated by a commerce sector. On the other hand, it is not supported by the real condition in the field that shows the opposite compared to the low percentage of commerce Zakat payer. Based on the reason, the author is triggered to investigate and to elaborate the complexity of Moslem’s decision in performing commerce zakat payment. This research relies on Multistage Sampling Method involved 100 participants by taking location at Malang. Furthermore, the accumulated data field is analyzed through Logit Method to identify the influential factor of the decision in Zakat payment. Processed data binary logit regression determines the most influential factor of Moslem’s decision in performing commerce zakat payment in Malang which relies on the level of income and their knowledge about Zakat’s scheme. According to this result, businessmen or traders who have high income level and moderate comprehension of laws, percentage, extrapolation, nisab, and paying period of commerce zakat have bridged up into a higher probability to perform commerce zakat. Whereas level of age, formal education, non-formal education, motivation, availability of Amil Zakat Institution (LAZ) and business period do not affect the decisions.Keywords: decision to perform Zakat, Commerce Zakat, Logit Analysis, Malang City